1998
DOI: 10.1074/jbc.273.42.27383
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-regulated Translocation of Endothelial Nitric-oxide Synthase

Abstract: The endothelial nitric-oxide synthase (eNOS) is activated by transient increases in intracellular Ca2؉ elicited by stimulation of diverse receptors, including bradykinin B 2 receptors on endothelial cells. eNOS and B 2 receptors are targeted to specialized signal-transducing domains in the plasma membrane termed plasmalemmal caveolae. Targeting to caveolae facilitates eNOS activation following receptor stimulation, but in resting cells, eNOS is tonically inhibited by its interactions with caveolin, the scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
144
0
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(162 citation statements)
references
References 25 publications
(16 reference statements)
15
144
0
3
Order By: Relevance
“…Consistent with previous immunofluorescence staining of eNOS in bovine aortic endothelial cells (40), we observed that the majority of cells exhibited a substantial immunoreactivity in the plasma membrane region, whereas a perinuclear staining was only found in a minority of cells. In contrast to this heterogeneous pattern of eNOS staining, the immunoreactivity against the NCX antibody did not exhibit considerable cell-tocell variations; as in all cells investigated, a substantial staining in the regions of the plasma membrane, the Golgi, and the cytoskeleton was observed.…”
Section: Role Of Nasupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with previous immunofluorescence staining of eNOS in bovine aortic endothelial cells (40), we observed that the majority of cells exhibited a substantial immunoreactivity in the plasma membrane region, whereas a perinuclear staining was only found in a minority of cells. In contrast to this heterogeneous pattern of eNOS staining, the immunoreactivity against the NCX antibody did not exhibit considerable cell-tocell variations; as in all cells investigated, a substantial staining in the regions of the plasma membrane, the Golgi, and the cytoskeleton was observed.…”
Section: Role Of Nasupporting
confidence: 79%
“…Interestingly, the proportion of caveolae-associated eNOS reported by these authors was ϳ35% and, thus, considerably lower than observed in the present study (ϳ90%). This variation in the subcellular distribution may be explained by variability of eNOS localization due to species differences, type of endothelial cells, or culture conditions (1,40).…”
Section: Role Of Namentioning
confidence: 99%
“…Our data provide evidence that the activation of eNOS translocation may be obtained for a longer time than eNOS phosphorylation. Accordingly, it could recently be shown that receptormediated Ca 2 þ -dependent eNOS translocation first reaches the maximum after 5 min and it can stay up to 20 min; this is longer than our observation time (Prabhakar et al, 1998), while a transient phosphorylation of eNOS at Ser1177 is known for not more than 5 min (Harris et al, 2001). Besides excitation-contraction coupling, different myocardial cellular and intracellular targets of NO necessary for myocardial maintenance and function could be shown, such as nerve fibers, resistance vessels and capillaries, as well as mitochondria (for a review, see Bloch et al, 2001a).…”
Section: Discussionmentioning
confidence: 49%
“…Firstly, proper subcellular localization of eNOS is critical for activation of eNOS by agonists [16]. In a resting state of endothelial cells, caveolae-bound eNOS is inactivated by interaction with caveolin-1, whereas upon receptor activation the resultant [Ca 2+ ] i elevation stimulates the dissociation of eNOS from caveolin-1, thereby activating eNOS [17]. This process has been considered to be a major mechanism for the Ca 2+ -dependent activation of eNOS in endothelial cells [18].…”
Section: Discussionmentioning
confidence: 99%